Unravelling the ESG-volatility nexus: a panel data analysis of Malaysia market - Thor, Yu Chao (2025)
In an era of heightened investor scrutiny and evolving market dynamics, the relationship between Environmental, Social, and Governance (ESG) performance and stock price volatility warrants in-depth investigation, especially in emerging markets such as Malaysia. This study addresses a critical gap in the Malaysian context, where research on ESG has predominantly focused on firm value and financial performance. This study aimed to investigate the relationship between ESG performance and stock price volatility in the Malaysian stock market, utilizing panel data analysis techniques on 1,800 firm-month observations. Given the rapid growth and evolving regulatory landscape of the Malaysian stock market, a deeper understanding of how ESG factors influence market risk is of paramount importance for all stakeholders.